PERAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DALAM MENINGKTKAN KUALITAS KEPEMIMPINAN DI SEKOLAH - Desi Kurniawati; Mohamad Muspawi; Elsika Sari; Nazwa Ayla Azzura (STKIP Subang, 2026)
Interpersonal communication plays a crucial role in supporting the effectiveness of school principals’ leadership. This study aims to analyze the role of principals’ interpersonal communication in improving leadership quality and supporting decision-making processes in educational settings. The method used is a qualitative approach through a literature review of relevant journals and academic books published between 2015 and 2025. The findings indicate that effective interpersonal communication—characterized by openness, empathy, and clarity of information—can enhance trust, teacher participation, and the quality of decision-making. Furthermore, good communication contributes to the creation of a conducive and collaborative working environment. Therefore, interpersonal communication is a key competency that must be possessed by school principals to improve leadership quality and educational outcomes